Avaliação pós ocupação para o centro de reabilitação do Amapá - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2018)
The Centro de Reabilitação do Amapá (CREAP) is the first Specialized Rehabilitation Center (SRC) created in the city of Macapá to promote, in the best possible way, the recovery of people who have some kind of sequela due to pathologies or traumas. However, it has been located in the same building for almost 20 years, which has undergone few structuring interventions, leading to the outdated building in relation to the applicable standardization and the patients' own demand. To identify the existing problems, a Post-Occupancy Assessment (POA) was developed, through: photographic survey; interviews with employees and patients, through the application of open and direct questionnaires; survey of the structure of the building through in loco footage; in addition to investigating the applicable legislation and case studies of other SRC references in the provision of this type of service. With POA, an investigative method was created through the analysis of structuring factors, so that a diagnosis could be established aiming at proposing possible improvements to be implemented. With the elaboration of the intervention proposal, through a rehabilitation project of the Center, a physical structure was created that maintained and rehabilitated the main building, and created new blocks so that CREAP could meet ANVISA's requirements for SRC classification level. It is concluded that the POA is an important tool for the identification and verification of possible problems that a building may present, whether due to design error or even through lag after prolonged use, and that CREAP, with due attention to the details and elaboration of the appropriate project, it can return to meet the specifications of the applicable standards and provide its services in the best possible way.
Keywords: Centro de Reabilitação do Amapá (CREAP); Projeto de reabilitação; Avaliação pós-ocupação; Análise estrutural (Engenharia); CNPQ::CIENCIAS SOCIAIS APLICADAS